Techniques and Assessment of Small Business Capital - Narayanan, SR; Arthi, D (Ethiopian Journal of Science and Technology, 2025)
All businesses must have capital in order to purchase assets and maintain their operations. In general there are two types of capitals. In the case of debt capital, the cost is the interest rate that the firm must pay in order to borrow funds. For equity capital, the cost is the returns that must be paid to investors in the form of dividends and capital gains. The small business owners to determine a target capital structure for their firms. As a rule, the cost of capital for small businesses tends to be higher than it is for large, established businesses. The capital structure concerns the proportion of capital that is obtained through debt and equity. The optimal capital structure is the one that strikes a balance between risk and return and thereby maximizes the price of the stock and simultaneously minimizes the cost of capital. When evaluating a small business for a loan, lenders ideally like to see a two-year operating history, a stable management group, a desirable niche in the industry, a growth in market share, a strong cash flow, and an ability to obtain short-term financing from other sources as a supplement to the loan.